2011
DOI: 10.1260/0144-5987.29.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of High Rank Coalbed Methane Reservoir from the Xiangning Mining Area, Eastern Ordos Basin, China

Abstract: For the purpose of better estimating the CBM resource potential in the study area, the high rank CBM reservoirs were studied by geological surveys and laboratory measurements in Xiangning mining area, eastern Ordos Basin. Geological characteristics of coals in the Xiangning mining area provide favourable conditions for the development of CBM reservoirs. Coal seams are dominated by semibright coal, which are all low volatile anthracite coal with R max ranging from 2.22 to 2.50%. No. 2, 3 and 10 coal seams are v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…1 Location of the Liulin District in China. The map is modified from Ding et al (2011) Eastern Ordos Basin (Fig. 1).…”
Section: Study Site and Sample Collectionmentioning
confidence: 99%
“…1 Location of the Liulin District in China. The map is modified from Ding et al (2011) Eastern Ordos Basin (Fig. 1).…”
Section: Study Site and Sample Collectionmentioning
confidence: 99%
“…The characteristics of pore structures in coal are related to many factors, including the coal's degree of metamorphism (Bustin and Clarkson 1998;Prinz et al 2004;Prinz and Littke 2005;Tang et al 2008;Zhou and Wu 2012;Ding et al 2011;Gürdal and Yalçın 2001), degree of deformation Ogawa 2001, 2003;Jiang et al 2011;Xue et al 2012;Qu and Wang 2010), macerals (Zhou and Wu 2012;Gürdal and Yalçın 2001;Cai et al 2011;Mastalerz et al 2008), and minerals (Zhou and Wu 2012). Many scholars have conducted a tremendous amount of research in this aspect.…”
Section: Introductionmentioning
confidence: 99%
“…Many scholars have conducted a tremendous amount of research in this aspect. Among them, most are about the effects of metamorphism on the pore system of coal (Bustin and Clarkson 1998;Prinz et al 2004;Prinz and Littke 2005;Tang et al 2008;Zhou and Wu 2012;Ding et al 2011;Gürdal and Yalçın 2001). CO 2 isothermal adsorption experiments conducted by Bustin and Clarkson (1998) showed that as coal rank increased, the volume and surface area of micropores (<2 nm) in coal samples decreased initially and then increased and reached the minimum at the bituminous coal stage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coal-bed methane (CBM) can be thought as an important potential resource after changing from hazard to resource (Flores, 1998) and has been studied for many years since the late 20 th century (Bustin and Clarkson, 1998;Ding et al, 2011). To assess the gas content and mining safety, the factors of controlling gas distribution has been Coal seams in the researched region are mainly characterized with middle ash and sulfur, but some deeper buried coals, such as Nos.…”
Section: Introductionmentioning
confidence: 99%